The Revolution of Brix 3000 as Chemomechanical Caries Removal (Cmcr) Agent, A Scoping Review - Dewi, Aninda Kartika; Gartika, Meirina (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Traditional caries removal techniques, like using a vibrating drill, have several drawbacks, including unpleasant sensations, heat that can irritate dental pulp, the need for local anesthesia, high energy consumption, and environmental concerns. A new method, CMCR (chemomechanical caries removal) with Brix 3000, aims to address these issues. It is minimally invasive, painless, and comfortable, promoting a positive attitude towards dental care, especially for pediatric patients, those with anxiety or fear, and high-risk medical patients. Objective: This literature review examines the use of Brix 3000 gel for chemomechanical caries removal. Methods: The study uses a scoping review method, conducting a comprehensive literature search on PubMed, EBSCO, ScienceDirect, Scopus, ClinicalTrials.gov, and Google Scholar databases. The search focused on articles from the last 10 years using keywords like "chemomechanical caries removal," "Papain Based Gel," "Brix 3000," and "Dental caries." Results: Brix 3000 is the latest effective, efficient, and non-cytotoxic CMCR method. It has a shorter application time and lower cytotoxicity compared to other methods. It is the only CMCR agent using Encapsulating Buffer Emulsion (EBE) technology, enhancing proteolysis to remove degraded collagen from infected dentin. Brix 3000 is easy to use, requires no special instruments, offers patient comfort, does not need local anesthesia or drills, and does not irritate healthy tissue. Conclusion: Brix 3000 gel is an effective and efficient chemomechanical agent for caries removal.